Hypolipidemic effect of black rice (Oryza sativa L. indica) on HDL level in C57BL/6 (Mus musculus) mice with diabetes - Elmo Krisnawan; Yanuarita Tursinawati; Afiana Rohmani (Nusantara Science and Technology Proceedings, 2024)
Type 2 diabetes mellitus (T2DM) patients show insulin resistance which can increase lipolysis. This condition increases low-density lipoprotein (LDL) and a decrease in high-density lipoprotein (HDL). Black rice contains anthocyanin, amylose, and fiber, which are important to manage cholesterol levels, including HD. This research aims to investigate the hypolipidemic effect of black rice on HDL-level mice with T2DM. This experimental research involved 32 male mice which were divided into four groups, KN with four grams of standard feed per day; K(-) with four grams of standard feed per day; P(1) with 1.68 grams of cooked black rice, 2.32 grams of standard feed per day; P(2) with 3.36 gram of cooked black rice, 0.64 grams of standard feed per day. K(-), P(1), and P(2) were injected with streptozotocin (STZ)-nicotinamide (NA) once. The intervention was done in 28 days. The HDL level was measured pre and post-intervention. Paired t-test and ANOVA were used to analyze with p<0.05 as significant. There was a significant difference in HDL pre and post-test in the KN (p=0.002), K(-) (p=0.002), P(1) (p=0.000), and P(2) (p=0.000). A significant difference in HDL levels was found among groups before the intervention (p=0.026), after the intervention (p=0.000), and the difference in HDL level (p=0.000). The largest change in HDL levels was found at P(2) with an increase of 18.88 mg/dl. Giving black rice, 3.36 grams of black rice, and 0.64 grams of standard feed has a greater effect on changes in HDL in T2DM mice. Black rice can be a promising functional food for the alternative treatment of diabetes in later life at certain doses. Further research is needed to measure phytochemical content by adding variations in black rice substitution and treatment duration.